2021
DOI: 10.3389/fendo.2021.674704
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Sustained Upregulated Unimolecular GLP-1 and CCK Receptor Signalling in Obesity-Diabetes

Abstract: Combined activation of GLP-1 and CCK1 receptors has potential to synergistically augment the appetite-suppressive and glucose homeostatic actions of the individual parent peptides. In the current study, pancreatic beta-cell benefits of combined GLP-1 and CCK1 receptor upregulation were established, before characterising bioactivity and antidiabetic efficacy of an acylated dual-acting GLP-1/CCK hybrid peptide, namely [Lys12Pal]Ex-4/CCK. Both exendin-4 and CCK exhibited (p<0.001) proliferative and anti-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…CCK-resistance in obesity is evident, making obese individuals less sensitive to CCK’s satiety effect [ 58 ]. The biological action profile of CCK has strong parallels with those of GLP-1 [ 56 ], and a combined activation of their receptors induces body-weight reduction and blood-glucose control [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCK-resistance in obesity is evident, making obese individuals less sensitive to CCK’s satiety effect [ 58 ]. The biological action profile of CCK has strong parallels with those of GLP-1 [ 56 ], and a combined activation of their receptors induces body-weight reduction and blood-glucose control [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, administration of the beta-cell toxin, streptozotocin (STZ), can counter beta-cell compensation and prevent such innate adaptations ( Furman 2015 ). Thus, HFF mice with STZ-induced compromised beta-cells are characterised by obstruction of the classical beta-cell hypertrophy in response to prolonged high-fat feeding ( Tanday et al 2021 ). Therefore, this HFF-STZ murine model represents an ideal tool to fully explore the positive effects of peptide-based GCGR antagonists in obesity-driven forms of diabetes, where restoration of functional beta-cell mass would be highly advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this HFF-STZ murine model represents an ideal tool to fully explore the positive effects of peptide-based GCGR antagonists in obesity-driven forms of diabetes, where restoration of functional beta-cell mass would be highly advantageous. Notably, the benefits of GCGR blockade are believed to require at least some residual beta-cell function ( Damond et al 2016 ), which would be the case for HFF-STZ mice ( Tanday et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study has confirmed that peripherally administered physiological doses of Frontiers in Veterinary Science frontiersin.org GLP-1 can reduce meal size in rodents and humans, and that postprandial plasma concentrations of GLP-1 can cause satiety in rodents and humans (19). The combined injection of GLP-1 and CCK (20) or coadministration of a glucagon-like peptile-1 receptor (GLP-1R) agonist with a cholecystokinin Receptor-1 (CCKR1) agonist (21)(22)(23) can inhibit appetite and reduce body weight. Our results were similar, we found that Hu sheep fed with RS exhibited significantly reduced feed intake, which was associated with high CCK and GLP-1 levels in their blood.…”
Section: Discussionmentioning
confidence: 86%